Self‐Supporting, Flexible, Additive‐Free, and Scalable Hard Carbon Paper Self‐Interwoven by 1D Microbelts: Superb Room/Low‐Temperature Sodium Storage and Working Mechanism - Hou, Bao‐Hua; Wang, Ying‐Ying; Ning, Qiu‐Li; Li, Wen‐Hao; Xi, Xiao‐Tong; Yang, Xu; Liang, Hao‐Jie; Feng, Xi; Wu, Xing‐Long (Advanced materials (Weinheim), 2019)
Hard carbon is regarded as a promising anode material for sodium‐ion batteries (SIBs). However, it usually suffers from the issues of low initial Coulombic efficiency (ICE) and poor rate performance, severely hindering its practical application. Herein, a flexible, self‐supporting, and scalable hard carbon paper (HCP) derived from scalable and renewable tissue is rationally designed and prepared as practical additive‐free anode for room/low‐temperature SIBs with high ICE. In ether electrolyte, such HCP achieves an ICE of up to 91.2% with superior high‐rate capability, ultralong cycle life (e.g., 93% capacity retention over 1000 cycles at 200 mA g−1) and outstanding low‐temperature performance. Working mechanism analyses reveal that the plateau region is the rate‐determining step for HCP with a lower electrochemical reaction kinetics, which can be significantly improved in ether electrolyte. A self‐supporting, flexible, additive‐free and scalable hard carbon paper (HCP) derived from tissue is rationally developed, and it achieves outstanding Na‐storage properties in terms of high initial Coulombic efficiency (91.2%), superior high‐rate capability, ultralong cyclic stability, as well as outstanding low‐T performance in ether electrolyte. More significantly, the Na‐storage and capacity attenuation mechanism of the HCP anode is revealed.